Effects of annealing in vacuum on the microstructure of silicon-containing calcium phosphate films deposited on a ZrNb alloy by radio-frequency magnetron sputtering; Vacuum; Vol. 212 - Surmeneva M. A. Maria Alexandrovna; Prosolov K. A. Konstantin Alexandrovich; Glukhov I. Ivan; Grubova I. Yu. Irina Yurievna; Botvin V. V. Vladimir Viktorovich; Surmenev R. A. Roman Anatolievich; Sharkeev Yu. P. Yury Petrovich (2023, 2023)
Title screen